Switching on the Fluorescence Emission of Polypyridine Ligands by Simultaneous Zinc(II) Binding and Protonation. Issue 4 (1st April 2020) - Conti, Luca; Giorgi, Claudia; Valtancoli, Barbara; Paoli, Paola; Rossi, Patrizia; Marchionni, Andrea; Faggi, Enrico; Bencini, Andrea
Abstract: The synthesis and characterization of the two new open‐chain ligands 1, 15‐ bis ‐[6‐(2, 2'‐bipyridyl)]‐2, 5, 8, 11, 14‐pentaaza‐octadecane (L1 ) and 1, 15‐ bis‐ [2‐(1, 10‐phenanthroline)‐9‐methyl]‐2, 5, 8, 11, 14‐pentaazaoctadecane (L2 ), both featuring a tetraethylenpentaamine chain linking via methylene bridges the 6 and 2 positions of two identical 2, 2'‐bipyridyl (bpy) and 9‐methyl‐1, 10‐phenanthroline (9‐methyl‐phen) moieties respectively, are reported. Their protonation and binding ability for Cu 2+, Zn 2+, Cd 2+ and Pb 2+ have been studied by coupling potentiometric titrations with UV‐vis absorption and fluorescence emission measurements in water. L1 and L2 afford stable mono‐ and dinuclear complexes, in which the metal ion is bound by a single bpy or 9‐methyl‐phen unit and the amine groups on the aliphatic chain. However, L1 displays a greater binding ability for Cu 2+ and Zn 2+ with respect to L2, the stability constants of the [ML1 ] 2+ complexes being 21.8 (Cu 2+ ) and 19.4 (Zn 2+ ) log units vs 20.34 and 16.8 log. units for the corresponding L2 species. Among all the metal ions tested, only the Zn 2+ complex with L2 features an enhanced fluorescence emission at neutral pH, thanks to the simultaneous binding of one Zn 2+ ion and H + ion(s), that inhibits any possible photoinduced electron transfer (PET) process from the amine donors to the excited phen moiety. Binding of a second metal switches off the emission again. Abstract : Finely tuned : The emission of Zn 2+ complexes with L2 is tuned by both metal ion and H + binding. Coordination of a single Zn 2+ ion maintains the system in its non‐emissive OFF state and only simultaneous binding of one metal cation and an H + ion switches ON the emission, which is, in turn, quenched again by the coordination of a second Zn 2+ ion. L2 results a peculiar molecular switch whose emission is modulated by both metal and proton binding.